Gender Lens on the Budget 2020-2021 - Hodgson, Helen; James, Amity; Blundell, Barbara; Coleman, Marie (National Foundation for Australian Women, 2020)
These position papers have been developed by NFAW’s Social Policy Committee to summarise 2020-2021 Budget measures of importance to women in Australia. It also contains a summary of modelling on the impacts of increased government expenditure in the care sectors – see Appendix A.